2007
DOI: 10.1086/518375
|View full text |Cite
|
Sign up to set email alerts
|

Searching for the Physiological Mechanism of Density Dependence: Does Corticosterone Regulate Tadpole Responses to Density?

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.. The University of Chicago Press ABSTRACTDensity-dependent population regulation is important in many natural populations, and in those populations, high population density is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
15
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 35 publications
(41 reference statements)
4
15
0
Order By: Relevance
“…Tadpoles from the highdensity tanks lacked changes in leukocytes that could account for increased susceptibility to infection, and neutrophil-to-lymphocyte ratios were higher in the highdensity mesocosms, opposite the effect predicted by stress-induced immunomodulation (Appendix D; Davis et al 2008). This result is consistent with previous studies, which have only found significant stress responses in tadpoles at much higher densities than used in this experiment (2-10 tadpoles/L; Hayes 1997, Glennemeier and Denver 2002, Belden et al 2007.…”
Section: Discussionsupporting
confidence: 94%
“…Tadpoles from the highdensity tanks lacked changes in leukocytes that could account for increased susceptibility to infection, and neutrophil-to-lymphocyte ratios were higher in the highdensity mesocosms, opposite the effect predicted by stress-induced immunomodulation (Appendix D; Davis et al 2008). This result is consistent with previous studies, which have only found significant stress responses in tadpoles at much higher densities than used in this experiment (2-10 tadpoles/L; Hayes 1997, Glennemeier and Denver 2002, Belden et al 2007.…”
Section: Discussionsupporting
confidence: 94%
“…couchii, it is not entirely clear which causal pathways link these variables. Our multiple regression analysis indicated that CORT concentrations varied inversely with body mass (and to a lesser extent with C. C. Ledón-Rettig, D. W. Pfennig and E. J. Crespi (Belden et al, 2007) and other vertebrates (Kitaysky et al, 1999;Moore et al, 2000). However, the effect of diet on Sc.…”
Section: Discussionmentioning
confidence: 72%
“…Our field survey results show baseline corticosterone concentrations differing significantly among freeliving A. jeffersonianum populations. Belden et al (2007) have also shown variations in baseline corticosterone concentrations among tadpoles in free-living wood frog Rana sylvatica populations. Differing baseline corticosterone concentrations could suggest that these populations are experiencing varied environmental stressors in their aquatic systems, similar to what was proposed for adult Ambystoma maculatum by Homan et al (2003).…”
Section: Discussionmentioning
confidence: 85%
“…Wingfield 1994), and amphibians (Homan et al 2003;Belden et al 2007), although population-level variation in baseline glucocorticoid concentrations is not always found (Pravosudov et al 2004).…”
Section: Pond Acidification and Corticosterone In Salamanders 225mentioning
confidence: 99%
See 1 more Smart Citation